The Mediating Role of Job Characteristics in the Relationship between Structural Empowerment and the Professional Commitment of Female Referees in Futsal Premier League - Javad Shahlaei Bagheri; Hassan Gharehkhani; Esmail Dolatyari (Shahid Bahonar University of Kerman, 2021)
The aim of this study was to develop a model for examining the mediating role of job characteristics in the relationship between structural empowerment and professional commitment of referees in female's Futsal Premier League. To collect the required data, we distributed the research questionnaires among 75 Futsal Premier League referees invited to the pre-season qualifying class in 2020, and finally we received 63 valid questionnaires. We conducted structural equation modeling, confirmatory factor analysis and path analysis for data analysis by using PLS Smart software. The findings demonstrated that structural empowerment can predict professional commitment, but the relationship between the two variables was not significant. The relationship of structural empowerment with job characteristics and professional commitment was not significant. The mediating role of job characteristics in the relationship between the two variables was not significant. The components of information sharing in structural empowerment, attachment to professional commitment and diversity of skills in job characteristics had the highest averages. Given that the lack of significance of the relationship among structural empowerment, professional commitment and job characteristics, is questionable and it should be assessed in great details.